Aktivitas Antibakteri Ekstrak Metanol Daun Sembung Rambat (Mikania micrantha H.B.K) Terhadap Pertumbuhan Bakteri Bacillus cereus IHB B 379 dan Shigella flexneri - Mukarlina, Rosalina Yuliana Ayen, Rahmawati, (Jurnal Protobiont, 2017)
Bacillus cereus and Shigella flexneri is a pathogenic bacterium that often contaminate food, can cause infection and digestive disorders. One of herbal plant which can be use as an antibacterial is sembung rambat (Mikania micrantha). This research aimed to determine the antibacterial activity of M. micrantha leaf methanol extract on the growth B. cereus IHB B 379 and S. flexneri. This research was conducted from Februari to April 2017. The testing of antibacterial activity has been performed using paper disk diffusion method with some extract concentrations of 0.45;0.50;0.55;0.60 and 0.65 g/ml and positive control of antibiotic chloramphenicol 0.003 Î¼g. The lowest concentrations of the extracts that have been able to inhibit the growth of B. cereus IHB B 379 are 0.65 g/ml and are 0.50 g/ml of S. flexneri with a very strong resitance response. The test result show that M. micrantha leaf methanol extract is bacteriostatic.